(untitled) (Research, Society and Development, 2021)
Academic leagues consist of multidisciplinary non-profit organizations with the aim of directly influencing the academic and social formation process of students, based on theories and practices in more depth. The present study aims to report and describe the challenges faced, the activities carried out and the perspectives of nursing students who are part of an academic League in the state of Piauí in 2020, during the pandemic caused by the Sars-CoV-2 virus, an approach clear about the need for adaptation, reframing and resilience, and may serve as an aid to other alloys and future ligands. In this period of social isolation, one realizes how irreplaceable the classroom and the physical presence are, it is clear that in the past knowledge is not limited to geographic spaces such as schools and universities. In fact, it was difficult to adapt to a reality of distance learning at a time when the presence in classrooms and the discussions provided there are essential to learning. However, it is understood that remote education is the most viable option at the moment, in this sense, education cannot stop and it is possible to minimize the impact of social isolation. Thus, even after substantial confrontation in the social and educational context, it is possible to understand the relevance of academic leagues due to the wealth of experiences provided through complementary knowledge and academic activities.